Momentum Investment Strategies, Portfolio Performance, and Herding: A Study of Mutual Fund Behavior - Grinblatt, Mark; Titman, Sheridan; Wermers, Russ (American Economic Review, 1995)
This study analyzes the extent to which mutual funds purchase stocks based on their past returns as well as their tendency to exhibit "herding" behavior (i.e., buying and selling the same stocks at the same time). We find that 77 percent of the mutual funds were "momentum investors," buying stocks that were past winners; however, most did not systematically sell past losers. On average, funds that invested on momentum realized significantly better performance than other funds. We also find relatively weak evidence that funds tended to buy and sell the same stocks at the same time.